CORRELATION OF T-CELL LYMPHOMA SUBTYPES WITH ANEMIA AT DR MOHAMMAD HOESIN HOSPITAL PALEMBANG 2018-2022 - Murti, Krisna; Saputra Naibaho, Oldyo; Farah Diba, Masayu; Kartika Edi Poedjo Purnamawati, Ika; Fauziah Kurniawaty, Nyiayu (Fakultas Kedokteran Universitas Sriwijaya, 2024)
Lymphoma is divided into Hodgkin lymphoma (HL) and non-Hodgkin lymphoma (NHL). Among NHL T-cell lymphoma is a rare malignancy of T cells, accounts for 12% of all NHL cases, it is further classified into 53 subtypes by WHO. T-cell lymphoma generally have worse prognosis than those B cells. In 2020 there were 16.125 new cases in Indonesia with 9.024 deaths for all ages and genders. Anemia occurs in some cases of lymphoma, which will make the prognosis of lymphoma worse. This study aims to determine the relationship between T-cell lymphoma subtype and anemia. This observational analytic study utilized a cross-sectional design conducted at the Department of Anatomic Pathology Faculty of Medicine Sriwiaya University/Dr. Mohammad Hoesin Palembang Hospital (RSMH) and the central laboratory of RSMH. The samples from this study were all patients who were diagnosed histopathologically and immunohistochemically as T cell lymphoma at RSMH Palembang from 2018 to 2022. Among 38 samples, T-cell lymphoma predominated in the age group <55 years (73,7%), male gender (73,7%), extranodal location (73,7%), and ENKTCL, nasal subtype (55,3%). Anemia occurred in 60,5% cases and most often it is mild anemia (60,9%). There was no significant correlation between T-cell lymphoma subtype and anemia status (*p = 0.178) and T-cell lymphoma subtype and anemia degree (*p = 0.342). It can be concluded that there is no significant correlation between the T-cell lymphoma subtype and anemia.